Movement as experience through mind. body. spirit. - Hubbard, Elise (Kansas State University, 2010)
In a nation of speedy and convenient technologies, the default pace of life has become “fast.” For many American cities, the primary mode of transportation is the private automobile. Daily life is conveniently seen through the car window: we drive to, drive-thru, and drive home. Auto-dependent growth patterns have evolved into sprawling networks of streets and low density, single land-use development. With few pedestrian amenities or destinations, long travel distances, and dominating automobile infrastructure, this development pattern decreases pedestrian and bicycle circulation as a viable and enjoyable mode of transportation. Transportation growth centered around the private automobile compromises compact development, physical activity, safety of pedestrians and bicyclists, interaction with nature, social exchange, and social equity in street corridors. Automobile circulation dominates the transportation system of Manhattan, Kansas. The result is low-density development, sprawling into the surrounding tall-grass prairie and flint hills of the region. Despite several City documents stating goals for multi-modal transportation and accommodation of all users, the existing built environment remains heavily dominated by automobile circulation. The current transportation system inhibits safe and enjoyable pedestrian and bicyclist transit. Inspired by Allan Jacobs’s Greet Streets vision and structured around the Institute of Transportation Engineers’ Context Sensitive Solutions, street networks can be public places for community: “people acting and interacting to achieve in concert what they might not achieve alone” (Jacobs 1993). Movement corridors should be public spaces that encourage physical activity and time to experience a healthier body, mind, and spirit. With priority for bicycle and pedestrian circulation, movement corridors support a more sustainable development pattern and foster meaningful time in transit through more natural speeds of engagement and active presence. Great streets for all users, and a means to integrate improvements in the planning and design of movement corridors will activate progressive growth. The action framework presented here emphasizes important elements concerning the vision for Manhattan’s movement corridors, shows how district development reinforces attributes for walkable communities, and demonstrates guidelines for integrating improvements in Manhattan’s transportation planning and design.
Keywords: Transportation planning; Landscape architecture; Movement as experience; Bicycle and pedestrian; Circulation; Manhattan Kansas; Landscape Architecture (0390)